Income Tax Over-Withholding and Household Investment Decisions - Chen, Xi; Kim, Jungbae; Lourie, Ben; Zhu, Chenqi (The Accounting Review, 2026)
ABSTRACT Over three-quarters of U.S. taxpayers receive federal tax refunds, largely due to income tax over-withholding. This study explores how over-withholding impacts investments by comparing individuals’ investment behavior following wage receipts and tax refunds. We find a significantly higher marginal propensity to invest out of wages than refunds, suggesting that over-withholding, which alters the labeling and timing of income, meaningfully influences financial decision-making. Our cross-sectional analysis indicates that the differential investment rates are more pronounced for individuals with automatic investment setups and lower financial sophistication. The difference cannot be fully explained by alternative explanations such as lack of awareness, fixed dollar investment goals, timing differences between wages and refunds, uncertainty of refunds, transaction costs, or the perception of refunds as additional windfall income. Our findings underscore the importance of considering behavioral factors in the formulation of tax policies and contribute to the accounting literature that examines taxes and investment behavior.